Students’ Perception on Micro-teaching Course at English Education Department of UIN SUSKA RIAU - Muhammad Rifki Hamim; Idham Syahputra (TRANSFORM: Journal of English Language Teaching and Learning, 2025)
The purpose of this research is to describe the students’ perception on micro-teaching and to determine students’ ability in micro-teaching course at sixth semester for students of English education department UIN Suska Riau. This research used quantitative design. The sample of this research were taken by random sampling. The population of this research is sixth semester students at the English education department of UIN Suska Riau. There were 26 students in total as the sample (20% from 126 students). In data collection, researcher used questionnaires and interview to collect data. The result of the research shows that the students’ perception on micro-teaching course is M=4.68 which is classified into very good category with students’ ability in teaching preparation is M=4.36 which is classified into very high level of category, students’ ability in preparation process (making RPP) is M=4.00 which is classified into high level of category, and students’ ability in explaining classified into enough level of category.